1982
DOI: 10.1055/s-2008-1055999
|View full text |Cite
|
Sign up to set email alerts
|

Formanalyse von 153 Mikroverkalkungsgruppen maligner Genese: Das „Dreieckprinzip”

Abstract: The forms and outlines of 153 clustered microcalcifications in 114 patients with histologically proven intraduct carcinomas were analysed. Seven groups could be defined; of these, a triangle principle"). The smaller groups tended to have straight margins, but the larger groups often showed wavy contours and at least one indentation at the base ("Swallow-tail phenomenon"). At the same time, the larger groups show circumscribed areas free of microcalcification, which correspond to interductal fat deposition. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We faced particular problems in the recommendation of a biopsy in patients with indeterminate microcalcifications in a round or oval cluster, according to our criteria H a BI-RADS H 3 lesion. Although LANYI claims that he has never observed a malignancy with round or oval distribution patterns in 153 clusters of microcalcifications (11), the distribution pattern ''round or oval'', particularly in small clusters with a diameter of 5 mm to 10 mm, cannot always be discriminated definitively from small regional/segmental distributions. As lesions in high-risk patients (for definition, see Material and Methods section) have a higher pretest probability for breast cancer per se, we recommend a vacuum core biopsy in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…We faced particular problems in the recommendation of a biopsy in patients with indeterminate microcalcifications in a round or oval cluster, according to our criteria H a BI-RADS H 3 lesion. Although LANYI claims that he has never observed a malignancy with round or oval distribution patterns in 153 clusters of microcalcifications (11), the distribution pattern ''round or oval'', particularly in small clusters with a diameter of 5 mm to 10 mm, cannot always be discriminated definitively from small regional/segmental distributions. As lesions in high-risk patients (for definition, see Material and Methods section) have a higher pretest probability for breast cancer per se, we recommend a vacuum core biopsy in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…The subgroup analysis showed a significant higher risk for lesions with more than 10 particles compared to less than 10 particles. Lanyi [4,62,64] found that microcalcifications with a round/oval disposition were less likely to be malignant than microcalcifications with geometric dispositions suggestive of the mammary ductal system (triangle principle). Analysis of the distribution of microcalcifications within clustered, round/punctate microcalcifications for risk stratification based on the earlier work of Lanyi was proposed by the consensus conference of the German Radiological Society [66].…”
mentioning
confidence: 99%